Smart nudging: How cognitive technologies enable choice architectures for value co-creation - Mele Cristina; Russo Spena Tiziana; Kaartemo Valtteri; Marzullo Maria Luisa (Elsevier, 2022)
People make decisions and take actions to improve their viability everyday, and they increasingly turn to artificial intelligence (AI) to assist with their decision making. Such trends suggest the need to determine how AI and other cognitive technologies affect value co-creation. An integrative framework, based on the service-dominant logic and nudge theory, conceptualizes smart nudging as uses of cognitive technologies to affect people’s behaviour predictably, without limiting their options or altering their economic incentives. Several choice architectures and nudges affect value co-creation, by (1) widening resource accessibility, (2) extending engagement, or (3) augmenting human actors’ agency. Although cognitive technologies are unlikely to engender smart outcomes alone, they enable designs of conditions and contexts that promote smart behaviours, by amplifying capacities for self-understanding, control, and action. This study offers a conceptualization of actors’ value co-creation prompted by AI-driven nudged choices, in terms of re-institutionalizing processes that affect agency and practices.